Quo Vadis Loss and Damage Fund After Cop28? - Zuhra, Amalia; Sabirin, Ahmad (ADPEBI International Journal of Business and Social Science, 2024)
One of the critical decisions of COP28 related to the L&D fund. Developing countries are confused. If the WB manages L&D, 12% of the fund will be deducted from the WB. If the fund is not managed correctly with World Bank standards, transaction costs, and leakage will result in the L&D fund losing a lot. Based on background, the paper examines how financing climate change L&D will work for developing countries. The findings in this paper show that if the WB manages the L&D fund. The fund management's independence, transparency, and effectiveness will likely be interfered with by certain countries with interests. Therefore, it is essential to publish an independent institution for managing and operating the distribution of L&D funds under the auspices of the UNFCC. In addition, the need for a particular chapter in the IPCC on L&D funds encourages and strengthens the seriousness of developed countries with the consistency of responsibility for the fund. Also, private companies that have interests or contribute the most to high emissions need to contribute to this fund. Furthermore, in the author's opinion, L&D funding is considered successful if it fulfills the following four things: consistency, clarity, community-driven, and corruption-free